Analisis Data Perkembangan Kasus Positif COVID-19 Di Jawa Barat Menggunakan Metode EDA (Exploratory Data Analysis) - Wardhani, Amalia Ayu (Jurnal Pengembangan Rekayasa dan Teknologi, 2022)
COVID-19 cases that have afflicted the people of Indonesia, especially West Java, have experienced an increase and decrease in confirmed patients with the COVID-19 virus. This caused the Data and Information Center of the Ministry of Health of the Republic of Indonesia to make observations to inform the number of confirmed, recovered and death cases to the Indonesian people using visualizations in the form of graphs. This study aims to determine the number of spikes in certain categories every week, identify the top five data every day and week, and find out the dynamics of COVID-19 cases by making a comparative graph between the accumulation of active, recovered, and dead cases using the Exploratory Data Analysis (EDA) method. As a result of this study, visualization in the form of a bar chart gives an overview of daily and weekly cases in West Java that have confirmed cases, deaths, and recoveries. Visualization in the form of a line chart gives a comparative picture of each daily and weekly case.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian  //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//
Keywords: COVID-19; Deltacron; Data Analysis; EDA; Omicron; Python; Jupyter